Do all matches require the same effort? Influence of contextual factors on physical demands during official female handball competitions - García-Sánchez, Carlos; Navarro, Rafael Manuel; Mon-López, Daniel; Nieto-Acevedo, Raúl; Cañadas-García, Enrique; de la Rubia, Alfonso (Biology of Sport, 2024)
Understanding the influence of contextual factors on physical demands is essential to maximize performance in handball. The purpose of this study was to explore and compare the influence of contextual factors (halves of the match, level of the opponent, match outcome and player role) on external load during official matches in women’s handball. Twenty-two semi-professional female players from the Spanish 2nd Division were monitored across 13 official home matches. Total distance covered (TDC), high-speed running distance (HSR), high-intensity breaking distance (HIBD), accelerations (ACC), decelerations (DEC) and PlayerLoad (PL) were collected in absolute and relative values (normalized by playing time) using a local positioning system (WIMU PRO, Realtrack Systems S.L., Almería, Spain). HSR, HSR/min and HIBD/min decreased during the second half ( p < 0.05; small effects). Regarding the level of the opponent, high-level and middle-level teams elicited higher TDC/min, HIBD/min and PL/min than low-level teams ( p < 0.05; small-moderate effects). Additionally, starter players exhibited higher absolute values of external load (TDC, HSR, HIBD, ACC, DEC and PL) compared to non-starters ( p < 0.05; moderate-large effects). Match outcome did not affect the physical demands ( p > 0.05). The study indicated that halves of the match, level of the opponent, and player role influenced external load experienced by players during official matches; specifically, starter players showed higher absolute values of external load compared to non-starters. This information should be considered in managing load and developing strategies to minimize fatigue and enhance performance during matches.